Влияние физико-химических воздействий на свойства шлифпорошков кубического нитрида бора - Соколов, А.Н.; Ильницкая, Г.Д.; Невструев, Г.Ф. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
As a result of the made researches it is positioned, that the concentrated and diluted with sulfuric, azotic, saline acids and as a mix of saline and azotic acids ("nitrohydrochloric acid") and solutions of oxyhydroxide of sodium and potassium do not render influence on cBN. At action of a melt of oxyhydroxide of sodium there is a decomposition cBN.